Technology assessment as a myth buster: deconstructing myths around emerging technologies. Issue 2 (4th May 2017) - Torgersen, Helge; Fuchs, Daniela
ABSTRACT: Responsible Research and Innovation requires the debating of emerging technologies 'upstream'. In discussions on radically novel technologies, comparisons with older technologies are often drawn. This leads to a transfer of assigned properties in the creation of rhetoric so that the new technology appears as a derivative of the older. Sometimes, several comparator technologies are at hand which may give the new technology a different image. Depending on the choices taken in rhetoric creation, a group of actors may acquire advantages over other groups, thereby establishing power relations and sometimes deciding the fate of the technology in question. In this paper, we analyse these processes through a 'hermeneutic' upstream technology assessment (TA) lens, while applying Roland Barthes' concept of myths creation. Using the case examples of synthetic biology and neuro-enhancement, we highlight the importance of the role of comparators and the multilayered character of myths. The potential role of TA as a 'myth buster' may render another task of TA, namely, stimulating a public debate, more difficult because the issue at stake may appear less salient.